Avaliação da atividade catalítica de óxidos cerâmicos na conversão de óleos vegetais - Libanori, Gabriela Santilli do Nascimento (Universidade Federal de São Carlos, 2011)
Organic pollutants are one of the major problems related to water and environmental pollution. Nowadays, vegetable oils represent a considerable source for water contamination. The search for new strategies to provide an appropriate treatment to organic effluents must be considered as a priority in the water decontamination, since it is predicted that the world is about to face scarcity of water resources. Along these lines, this work presents a detailed investigation on the photocatalytic activity of nanoparticles of semiconductor oxides on the conversion of vegetable oils. Firstly, studies concerning the photocalyitic activity of TiO2 have been performed, since it is the most used semiconductor oxide used on photodegradation processes. However, our experiments have shown that TiO2 nanoparticles are not an appropriate photocatalyst to the conversion of refined corn oil using ultraviolet radiation (200-280nm). Alternatively, additional investigations on the use of the transesterification reaction as a potential route for the conversion of vegetable oils were carried out. For this study, acid and basic semiconductor oxides, such as SnO2, TiO2, ZnO, CaTiO3 and CaO, have been synthesized through the polimeric precursor route and their photocatalytic activity were compared to commercially avaliable oxides. The conversion of corn oil was then assessed by means of 1H Nuclear Magnetic Resonance (1H-NMR). The results revealed that basic oxides, such as CaO and ZnO are the most efficient in the photodegradation process. Since CaO was just detailed studied regarding its activity in transesterification, a detailed study about ZnO in this process was done. In order to verify the influence of the synthesis method on the photocatalytic activity, a detailed study was performed by comparing ZnO obtained by different chemical routes, namely solvothermal, hydrothermal microwave and polymeric precursor methods, to the commercially available ZnO, supplied by Synth. The results showed that the synthesis method does not play a significant role on the ZnO photocatalytic activity. However, it has been demonstrated that the photodegradation process can generate both short- and long-chain esters, depending on the concentration of hydroxil groups on the oxide surface.
Evaluation of catalytic activity of ceramic oxides on the conversion of vegetable oils
Keywords: Físico-química; Nanopartículas; Materiais cerâmicos; Transesterificação; Fotocatálise; Óleos vegetais; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA